PENGARUH INTELLECTUAL CAPITAL DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN YANG DIMEDIASI OLEH PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2018-2022 - Maesaroh, Titik Maesaroh; Faridhatun Faidah; Rhealin Hening Karatri (Ikatan Dosen Menulis, 2023)
This research aims to examine the influence of intellectual capital and good corporate governance on company value which is mediated by profitability in banking companies listed on the BEI in 2018-2022. The intellectual capital variable is measured by VAIC, good corporate governance is measured by the board of commissioners, company value is measured by PBV, and profitability is measured by ROA. The method used in this research is a quantitative method. The population in this study are banking companies listed on the BEI in 2018-2022. The sampling technique uses purposive sampling. The sample in this research was 10 banking companies with a research period of 5 years, totaling 50. The data analysis technique used in this research used Structural Equation Model Partial Least Square analysis with SmartPLS 3 software. The results of the research showed that Intellectual capital had a positive and significant effect on company value, good corporate governance has no effect on company value, intellectual capital has a positive and significant effect on profitability, good corporate governance has no effect on profitability, profitability has a positive and significant effect on company value, profitability has been proven to mediate the effect of intellectual capital on company value, profitability has no able to mediate the influence of good corporate governance on company value.